Implementasi Kebijakan Pemerintah Terhadap Disiplin Aparatur Sipil Negara Kabupaten Sidenreng Rappang - ahmad mustanir; Andi Asmawati AR; Haeruddin Syarifuddin; Abdul Jabbar; Saifullah; Kamaruddin Sellang; Muhammad Rais Rahmat Razak; Monalisa Ibrahim; Akhwan Ali; Irwan (Journal Social Politica, 2021)
This study aims to determine the implementation of government policies on the discipline of the state civil apparatus at the Village Office in Baranti District, Sidenreng Rappang Regency. The sampling technique used was saturated sampling technique with a total sample of 23 people. Data collection techniques using observation, interviews, questionnaires, and literature study. Quantitative data analysis techniques used are frequency tabulation analysis and simple regression analysis with the help of SPSS 20.0 for windows program and Likert Scale. Based on the results of the questionnaire, it was obtained a recapitulation of the variables of government policy implementation, measured through indicators of the right policy, right implementer, right target, right environment, and right process, 41% included in the "good enough" category. The recapitulation of the discipline variable of the state civil apparatus is measured by indicators of time discipline, regulatory discipline, and responsibility discipline, 33% of which are included in the "less good" category. Based on the results of the processed simple regression analysis using SPSS 20.0 for windows, with the Summary Model obtained a value of 41% in the "good enough" category.